Path of knowledge: promoting the learning of the first law of thermodynamics and its applications through a serious game - Ruthinéia Alves do Nascimento; Rayanne Carla Alves do Nascimento; Fabiane Rodrigues Fernandes; Vinicius Vescovi (Revista Brasileira de Ensino de Física)
Thermodynamics is an area of physics intrinsically connected to understanding various everyday phenomena and is a fundamental pillar in the training of professionals in various fields. Despite its importance, the teaching and learning of thermodynamics encounters several obstacles. Thus, this study presents the development and application of a board game with the theme of classical thermodynamics. It was developed to minimize students’ difficulties in assimilating theoretical concepts related to the first law of thermodynamics and its applications. The proposed didactic material proved to be an effective tool for motivating students and improving their learning of the subject in a fun way.